The role of smart polymeric biomaterials in bone regeneration: a review - Xing, Yanghui; Qiu, Linhui; Liu, Danqing; Dai, Sihan; Sheu, Chia-Lin (Frontiers in Bioengineering and Biotechnology, 2023)
Addressing critical bone defects necessitates innovative solutions beyond traditional methods, which are constrained by issues such as immune rejection and donor scarcity. Smart polymeric biomaterials that respond to external stimuli have emerged as a promising alternative, fostering endogenous bone regeneration. Light-responsive polymers, employed in 3D-printed scaffolds and photothermal therapies, enhance antibacterial efficiency and bone repair. Thermo-responsive biomaterials show promise in controlled bioactive agent release, stimulating osteocyte differentiation and bone regeneration. Further, the integration of conductive elements into polymers improves electrical signal transmission, influencing cellular behavior positively. Innovations include advanced 3D-printed poly(l-lactic acid) scaffolds, polyurethane foam scaffolds promoting cell differentiation, and responsive polymeric biomaterials for osteogenic and antibacterial drug delivery. Other developments focus on enzyme-responsive and redox-responsive polymers, which offer potential for bone regeneration and combat infection. Biomaterials responsive to mechanical, magnetic, and acoustic stimuli also show potential in bone regeneration, including mechanically-responsive polymers, magnetic-responsive biomaterials with superparamagnetic iron oxide nanoparticles, and acousticresponsive biomaterials. In conclusion, smart biopolymers are reshaping scaffold design and bone regeneration strategies. However, understanding their advantages and limitations is vital, indicating the need for continued exploratory research.